(untitled) (Research, Society and Development, 2020)
Whey is a by-product of cheese making, rich in protein, lactose, and minerals, which can be processed and added to new products. The valorization of this by-product generates an effluent, rich in organic matter, which, if not properly treated before disposal in water resources, causes environmental impacts. Anaerobic digestion stands out in the treatment of this effluent, as it presents good results in the removal of organic load, is easy to handle, does not require much space, and generates biogas, which can be used to obtain energy in industry. However, anaerobic digestion does not provide good removal of persistent pollutants, such as nitrogen and phosphorus, requiring the application of post-treatment. Electrocoagulation appears as a method for removing these nutrients, as it does not require pH control, requires less energy, and has low sludge production. Thus, this work addresses a review about the development and application of anaerobic methods as an alternative for the treatment of the effluent obtained in the processing of whey, showing the efficiency of the treatment in the removal of COD and after the application of electrocoagulation in order to remove nutrients like nitrogen and phosphorus.